Effect of Ascorbic Acid on Cardiac Surgery-Associated Acute Kidney Injury Incidence - Djordjevic, Anze; Susak, Stamenko; Kotnik, Petra; Gorenjak, Mario; Knez, Zeljko; Antonic, Miha (The Thoracic and Cardiovascular Surgeon, 2022)
Objectives Acute kidney injury (AKI) is associated with higher perioperative mortality and morbidity. Oxidative stress has been proposed as a cause of postoperative AKI. Ascorbic acid (AA) supplementation was suggested as a novel and promising antioxidant. The aim of this study was to evaluate the capability of AA to reduce the incidence of postoperative AKI in cardiac surgery patients.Methods A prospective randomized trial was conducted in patients scheduled for on-pump cardiac surgery. Subjects in the AA group received 2 g of AA intravenously during the induction of anesthesia, 2 g before aortic cross-clamp removal and 1 g every 8 hours for five postoperative days (the JERICA protocol). Postoperatively, the patients were monitored for AKI and other complications. Malondialdehyde levels were monitored in a subpopulation of 100 patients to evaluate the effect of AA on oxidative stress level.Results The AA and control group consisted of 163 and 169 patients, respectively. The groups were well matched for baseline demographics and had similar intraoperative characteristics. The incidence of AKI in the AA and control group was 20.9 and 28.4%, respectively (p = 0.127). The estimated glomerular filtration rate did not differ between the study groups in the entire postoperative period. There was a trend toward higher malondialdehyde values with statistical significance on postoperative day 1 and lower in-hospital mortality in the AA group (0.6 vs. 4.1%, p = 0.067).Conclusion Our results do not support the effectiveness of AA supplementation in reducing the incidence of postoperative AKI in on-pump cardiac surgery patients.Clinical Registration Number This study was registered with the ISRCTN Registry under the trial registration number ISRCTN98572043.
Keywords: acute kidney injury; ascorbic acid; cardiopulmonary bypass; oxidative stress